The Impact of Macroeconomic Fundamentals on Shanghai Composite Property Index - LI, TIANYI (2020)
The real estate industry occupies an important position in China's economy. In recent years, due to the acceleration of real estate price growth and the fluctuation of the real estate stock market, the real estate industry has become the focus industry. This study compares China and the United States' real estate to get reasonable and applicable parts to batter control the development of China’s real estate market. Besides, many macroeconomic indicators are closely related to the real estate stock market. Simultaneously, the real estate stock market reflects the fluctuations of the real estate industry to a certain extent. Therefore, it is crucial to explore the impact of macro-economy on the real estate stock market. This paper mainly focuses on the macroeconomic effects on the Shanghai composite property index .